Escherichia coli Strains with Virulent Factors Typical for Uropathogens were Isolated from Sinuses from Patients with Chronic Rhinosinusitis—Case Report - Krawczyk, Beata (Pathogens, 2020)
Escherichia coli were isolated from three patients with chronic rhinosinusitis (CRS) by intraoperative sinus tissue biopsy. Taking into account the unusual replicative niche and previous treatment failures, it was decided to focus on the virulence and drug resistance of these bacteria. The strains turned out to be multi-sensitive, but the rich virulence factors profile of bacteria typical for phylogenetic group B2 deserved attention. Tests were carried out for the presence of 32 genes using the PCR method. Particularly noteworthy are the toxins Cnf-1, HlyA, Usp—an extensive iron uptake system (enterobactin, salmochelin, yersiniabactin and outer membrane hemin receptor ChuA)—SPATE autotransporters such as vat and pic, Ag43 autoaggregative protein—important for biofilm formation—and TosA/B which enhance the fitness of E.coli. All these virulence factors are identified predominantly in UPEC strains and provide a fitness advantage during colonization of the sinuses. Patients with CRS should be asked for past or present UTI. The specific virulence factors of E. coli that facilitate the colonization of the GI tract and urinary tract may also favor the colonization of a new ecological niche (sinuses) as a result of microbial imbalance or dysbiosis.